Weight training for life - Hesson, James L. (Morton Publishing, 1995)
This book is ideal for anyone interested in learning about weight training. It is designed to help men and women of all ages build a solid foundation of current knowledge and practice in weight training and learn the most effective ways to develop their desired body shapes. The text contains full-color photos of "real people" demonstrating proper techniques. It also contains forms for writing goals, for planning a personal weight-training program, and for recording circumference measurements, strength measurements, and muscle endurance measurements. Readers will learn how to design and maintain a safe, personalized, effective, and enjoyable weight-training program. They will learn that weight training, done properly, can be a fun and beneficial activity.